Wealth Taxation and Charitable Giving - Marius A. K. Ring; Thor Olav Thoresen (Center for Economic Studies and ifo Institute (CESifo), 2022)
We provide novel evidence on the linkages between capital taxation and charitable giving on three fronts. First, we use quasi-experimental variation in the annual Norwegian wealth tax to study the effect on how much households give. Inconsistent with the notion that households give more in order to reduce future wealth taxes, we find a small negative effect. This is effect is entirely driven by households paying more in wealth taxes. The extensive-margin variation has no effect, which suggests an absence of intertemporal substitution effects in giving. Second, we study bunching at an income-tax exemption threshold for giving and estimate a modest own-price elasticity that is decreasing in income, age, and wealth. Third, we show that these nominally unrelated tax incentives interact: wealth taxation increases the after-tax own-price elasticity of giving. Overall, our evidence is consistent with modest effects of capital taxation on charitable giving that are primarily driven by income effects.
Keywords: H24; H31; H41; D64; 330; charitable giving; wealth taxation; tax incentives